Beyond Efficacy Signals: Regulatory, Methodological, and Translational Challenges in Clinical Research on Ketamine and Psilocybin in Psychiatry - Damian Swieczkowski; Michal Pruc; Lukasz Szarpak; Aleksander Kwaśny; Wiesław Jerzy Cubała (Psychiatry International, 2026)
Major depressive disorder (MDD) and treatment-resistant depression (TRD) continue to drive interest in ketamine-family compounds and psilocybin, but antidepressant efficacy alone does not establish whether these interventions can be evaluated reliably or implemented responsibly. We conducted a structured narrative review using targeted PubMed/MEDLINE searches through 21 July 2026, hand-searching of reference lists, and review of current regulatory documents. Six studies conducted by the authors formed the empirical foundation, covering trial protocols, dose–response relationships, treatment context reporting, regulatory alignment, participant diversity, and informed-consent readability. Findings were synthesized across regulatory, internal methodological, contextual, external, ethical, and implementation domains. The six studies identified recurring weaknesses in protocol design, dose and endpoint selection, masking and expectancy assessment, safety monitoring and long-term follow-up, reporting of psychological support and treatment setting, participant representativeness, and consent comprehensibility. The wider literature broadly supports these conclusions. Ketamine has a more mature evidence and implementation base, whereas psilocybin remains at an earlier stage of clinical development. Responsible translation into clinical practice therefore requires integrated evidence addressing efficacy, causal validity, safety, treatment context, diversity, informed consent, durability, and service delivery, while clearly distinguishing legal requirements, regulatory guidance, evidence-based methodological practices, and the authors’ recommendations.